2011
DOI: 10.1007/s00013-011-0278-6
|View full text |Cite
|
Sign up to set email alerts
|

A note on element orders and character codegrees

Abstract: The result of this note is as follows. If a finite solvable group has an element of order m, then the group has an irreducible character whose codegree contains all prime divisors of m.Mathematics Subject Classification (2010). Primary 20C20, 20C15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…On the other hand, by [8] and [6] (or [12]), As the proof above illustrates, this "gluing" process is an obstacle to obtaining best possible bounds in any variation of the 𝜌-𝜎 conjecture for arbitrary groups. It would be interesting to find some new idea that avoids this argument.…”
Section: Proofsmentioning
confidence: 99%
“…On the other hand, by [8] and [6] (or [12]), As the proof above illustrates, this "gluing" process is an obstacle to obtaining best possible bounds in any variation of the 𝜌-𝜎 conjecture for arbitrary groups. It would be interesting to find some new idea that avoids this argument.…”
Section: Proofsmentioning
confidence: 99%
“…/ D 1 if and only if D 1 G . Given [5] and [9], it is not surprising that the exponent of the derived factor group will influence the codegrees occurring in cod.G/.…”
Section: Basicsmentioning
confidence: 99%
“…In [9], Qian showed that if G is a solvable group and g 2 G, then there exists 2 Irr.G/ so that every prime divisor of o.g/ divides cod. /.…”
Section: Introductionmentioning
confidence: 99%
“…In his recent paper [2] in this journal, Guohua Qian proved the following theorem under the additional hypothesis that the group G is solvable. The purpose of this note is to give an easy proof with no solvability assumption.…”
Section: Mathematics Subject Classification (2010) 20c15mentioning
confidence: 99%